The Administration of Educational Opportunity Expansion School Using Information Technology Base under Nonthaburi Primary Educational Service Area O - Liwweha, Sasivimon; Petchroj, Laddawan (Journal of Humanities and Social Sciences, Rajapruk University, 2022)
This research aimed to study schools’ management of educational opportunities expansion using an information technology base classified by operation steps and structures under the Nonthaburi Primary Education District Office and to compare schools management according to administrator and teacher opinions classified by gender, education level, and age. The sample, stratified random sampling was 275 administrators and teachers in the school expanding their opportunities under the Nonthaburi Primary Education District Office. The instrument used in the research was a questionnaire with a straight value of 0.78 and a precision of 0.88. Statistics used to analyze data included percentage, mean, standard deviation, t-test, One-Way ANOVA, and LSD. The research results were found as followed: 1) School administration extends educational opportunities by using information technology as a base under the Office of Nonthaburi Primary Educational Service Area was at the highest level overall and with the operating step according to the management plan followed by a step of supervision, monitoring, and evaluation. Meanwhile, operating structural management planning found that academic management had the highest mean. 2) The results of the comparison showed that administrators and teachers had opinions on the administration. There was a statistically significant level of .05 according to gender, age, and educational background.